KONDISI PEKERJA SENIOR PASCA PENSIUN SETELAH DIKARYAKAN KEMBALI DALAM PERUSAHAAN MANUFAKTUR JEPANG - Dewi Saraswati Sakariah (Universitas Diponegoro, 2016)
This study discusses about the condition of the re-employed senior workers after retirement in Japan’s manufacturing companies. Since experiencing demographics problems, Japan faces many obstacles, one of them in the employment sector. Meanwhile, the government more incentive to make efforts to make Japan's rise from the stagnant economic situation after the economic recession since the 1990s. One of them by employing returning senior workers who have retired. The age of workers in Japan's pensions set by the government at the age of 60 years and the government is trying to raise the limit. Policies readmission of senior workers in the manufacturing companies of Japan after retirement is the type of work contract system. With a logical consequence of the creation of a number of different conditions with the conditions of the workers before retirement. The most prominent difference is the condition of the status of work and reduced the salary given up to 50% as a result of the worker's status has changed. However, there are still some conditions such as the number of hours worked, the same job. And on the part of senior workers have a good respon to their readmission policies in the company to support the employment sector in Japan. To obtain primary data, the authors distributed questionnaires to employees of manufacturing companies who are above the age of 60. In addition, the authors also conducted interviews to a number of parties for additional data.